The Acquisition of Translation Competence. Competences, Tasks, and Assessment in Translator Training - Hurtado Albir, Amparo (Meta, 2015)
The aim of this paper is to present the fundamental aspects of competence-based translator training. It begins with an overview of research on Translation Competence (TC) and its acquisition (ATC), with particular emphasis on the PACTE group’s TC and ATC models, which have been validated through experimental research. It subsequently deals with four cornerstones of competence-based translator training, namely the pedagogical approach called competence-based training; specific competences in translator training; the translation task and project-based approach as a methodological and curriculum design framework; and competence assessment in translator training. The paper provides examples of how to design translator training curriculums that centre on competence development and establishes assessment guidelines.